Research on the influence of human capital and social capital on subjective and objective employment quality paths of graduate students in China - Zhang, Tao; Gao, Rong; Yang, Shiyuan; Shi, Chengyuan (Frontiers in Education, 2025)
Employment is the biggest project of people’s livelihood. The high-quality employment of postgraduates is of practical significance to the supply of high-level talents and economic development. There is an urgent need for higher education to explore the critical path to improve the employment quality of postgraduates more effectively. In this study, 778 graduate students and hierarchical regression analysis were used to investigate the impact of human capital and social capital of graduate students on subjective and objective employment quality. The results show that human capital positively influences objective employment quality, and social capital positively influences subjective employment quality. Employability mediates the relationship between human capital and objective employment quality. It mediates between social capital and subjective employment quality. Future career clarity positively moderated the relationship between human capital and graduate student employability. Employment policy support negatively moderated the relationship between graduate student employability and subjective and objective job quality. This study reveals the mediating and boundary effects of graduate student “Capital” on employment quality and provides some references for graduate student training and employment.